Design of a Real-Time Indoor Positioning System Based on Visible Light Communication - Lima Junior, Marcos S. P. dos S.; Halapi, Miklos Peter; Udvary, Eszter (Společnost pro radioelektronické inženýrství, 2020)
In this paper a real-time Indoor Positioning System (IPS) based on Visible Light Communication (VLC) is proposed, deployed and studied. It is composed of nine LED-based VLC transmitters instaled in the ceilling of an indoor invironment, each of them transmitting different ID codes that are detected by a photodiode-based mobile correlator receiver. The receiver is able to measure the distance between itself and the transmitters and use this information to estimate its own position in the environment. The distances are measured using Received Signal Strength (RSS), where initial experiments were executed in order to determine physical parameters of the system. Then, the 2D or 3D position is estimated by the receiver using multilateration in real-time. This paper also brings tests and discussions regarding the accuracy achieved by the deployed system.
Keywords: Indoor Positioning Systems (IPS); Visible Light Communications (VLC); Received Signal Strenght (RSS); multilateration